Effect of Desensitizing Mouth Rinses on Surface Properties of 3D-Printed Crowns: An In Vitro Study - Agarwal, Uravi (2026)
This study evaluates the effect of desensitizing mouth rinses on the surface properties of 3D-printed crowns compared to heat-cured and cold-cured crowns. Thirty dental crowns were fabricated and divided into three groups: 3D-printed crowns, heat-cured crowns, and cold-cured crowns (n=10 each). All samples underwent daily immersion in a desensitizing mouth rinse (Senquel AD) for four weeks. Surface roughness, hardness, and color stability were analyzed pre- and post-treatment using a profilometer, Vickers hardness tester, and spectrophotometer. Statistical analyses were performed using ANOVA and post-hoc tests. 3D-printed crowns showed a significant increase in surface roughness and a reduction in hardness after exposure to the mouth rinse, while heat-cured crowns exhibited minimal changes. Cold-cured crowns demonstrated moderate alterations in surface properties. Color stability was unaffected in all groups. Desensitizing mouth rinses exert differential effects on dental crowns. While 3D-printed crowns are more susceptible to changes, heat-cured crowns retain superior surface stability. This underscores the importance of material-specific considerations when prescribing mouth rinses to patients.